REKONDISI RANGKAIAN KELISTRIKAN SISTEM PENGAPIAN PADA ENGINE DAIHATSU CHARADE G11 - , SAMUEL GINTING, Ir.Susanto Johanes, MT. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Todayâs ignition system is the most important things on cars. Internal combustion engine result in energy by burning the air and fuel mixture in the cylinder. The gasoline engine, the spark jumps the spark plug is needed to ignite the air-fuel mixture that has been compressed by the piston in the cylinder. If the wiring ignition system on engine is not properly maintain,it will not be produced good combustion too. Finally, reconstruction wiring ignition system was considered for the final project. The research has been done about reconstruction of wiring ignition system engine trainer Daihatsu Charade G 11. The previous conditionâs of engine trainer Daihatsu Charade G 11 is can not be oprated on because has many problems with the spare part and the wiring ignition system of the engine. Therefore, the part that have been malfunction was replaced with the new one. There is not only the part, but also related with wiring ignition system of the engine trainer. From the results of this final project, it can be concluded that the engine trainer Daihatsu Charade G 11 has in a good performance and can be implemented for improving more knowledge about the automotive.